PENGEMBANGAN PERANGKAT MODEL PROBLEM BASED LEARNING DENGAN GOOGLE CLASSROOM UNTUK MENINGKATKAN PENGUASAAN KONSEP SUHU DAN KALOR PESERTA DIDIK - Eka Nur Wulandari Abdullah; Sutrio; Syahrial Ayub; Aris Doyan (Postgraduate, University of Mataram, 2024)
This research aims to produce Problem Based Learning model learning tools using Google Classroom that are feasible, effective and practical to improve students' mastery of concepts in temperature and heat material. This type of research is development research (Reasearch and Development) using a 4D model (Define, Design, Development and Disseminate). The products that have been developed in this research are syllabus, RPP, LKPD, Google Classroom, and concept mastery test instruments. Data on the feasibility, effectiveness and practicality of learning tools were obtained from feasibility tests, N-gain tests and practicality tests. Feasibility data was obtained from the assessment of 6 validators consisting of 3 expert validators from Physics Education Lecturers at Mataram University and 3 practitioner validators from Physics Teachers at SMAN 3 Mataram. Effectiveness data was obtained from the results of the N-Gain test conducted on 17 students at SMAN 3 Mataram. Practicality data was obtained from observations of learning implementation and student response questionnaires. The results of the device feasibility test analysis were obtained at 89.70% with very feasible criteria. The results of the effectiveness test analysis using the N-gain test results were obtained at 73%, which is in the high category and the criteria are quite effective. The practicality test results were obtained at 90% with very practical criteria. Based on the results of the data analysis that has been obtained, it can be concluded that the learning tools that have been developed using the Problem Based Learning model with Google Classroom are declared feasible, effective and practical for increasing students' mastery of concepts in temperature and heat material.